Overexpression of Cancer Upregulated Gene 2 (CUG2) Decreases Spry2 Through c-Cbl, Leading to Activation of EGFR and _-Catenin Signaling - Natpaphan Yawut; Chutima Kaewpiboon; Phatcharaporn Budluang; Il-Rae Cho; Sirichat Kaowinn; Sang Seok Koh; Young-Hwa Chung (My University, 2020)
The mechanism by which cancer upregulated gene 2 (CUG2) overexpression induces cancer stem cell-like phenotypes is not fully understood. Because the increased activity and expression of epidermal growth factor receptor (EGFR) kinase have been reported in A549 cancer cells overexpressing CUG2 (A549-CUG2) compared with control cells (A549-Vec), the Sprouty2 (Spry2) protein has gained attention as the downstream molecule of EGFR signaling. Therefore, we aim to identify the role of Spry2 in CUG2-overexpressing lung cancer cells.Spry2 expression levels were examined in A549-CUG2 and A549-Vec cells by Western blotting and qRT-PCR. Cell migration, invasion, and sphere formation were examined after Spry2 suppression and overexpression. EGFR-Stat1 and Akt-ERK protein phosphorylation levels were detected via immunoblotting. NEK2 kinase and β-catenin reporter assay were performed for downstream of Spry2 signaling.Although A549-CUG2 cells showed lower levels of the Spry2 protein than A549-Vec cells, no difference in levels of Spry2 transcript was observed between both cells via qRT-PCR. Furthermore, MG132 treatment enhanced the protein levels and ubiquitination of Spry2, suggesting that Spry2 protein expression can be regulated via the ubiquitin-proteasome pathway. The enforced expression of c-Cbl, known as the binding partner of Spry2, decreased the Spry2 protein levels, whereas its knockdown oppositely increased them. Epithelial-mesenchymal transition (EMT) and sphere formation were increased in A549-Vec cells during Spry2 siRNA treatment, confirming the role of Spry2 in CUG2-induced oncogenesis. Furthermore, EMT and sphere formation were determined by the Spry2 protein levels through the regulation of EGFR-Stat1 and β-catenin-NEK2-Yap1 signaling pathways.CUG2 reduces Spry2 protein levels, the negative signaling molecule of cell proliferation, via c-Cbl, possibly activating the EGFR and β-catenin signaling pathways and, in turn, contributing to the induction of cancer stem cell-like phenotypes.
Keywords: Cancer, Hypoxia, and Metabolism